ANALISIS TENTANG NILAI – NILAI PANCASILA DI DALAM EKSTRAKURIKUER PRAMUKA DI SMKN 4 PEKANBARU - Handrayani, Lusi; Eddison, Ahmad; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research explains about the analysis Pancasila values. The implementation of the values of Pancasila is an obligation for the people of Indonesia, especially Scout members. Based on the results of observations (preliminary studies) carried out at SMK 4 Pekanbaru students who took part in scout extracurricular activities have been going very well. Based on interviews with trainers and assistant trainers at SMK 4 Pekanbaru, an analysis of the value of Pancasila in the Extracurricular Scouts has been going very well. Where students are trained to grow the values of Pancasila (values of divinity, humanity, unity, society and justice). Such as performing ceremonies carried out before and after starting Scout training, Line-up Training (LBB), adventure (nature exploring), camping, games, rigging and so on. This type of research used in this research is quantitative descriptive research type and the method used is a survey method, Data collection techniques with questionnaires and interviews. Data analysis uses percentage formulas . Based on the results of the research from chapter IV above, it can be concluded that this research is Pancasila values analyst in scout extracurricular activities at SMNK 4 Pekanbaru has done very well. This can be seen from the results of research which states that 90% of all members of the scout smkn 4 weeks just answered "yes" and the answer proves that the analysis of the values of pancasila in the scout extracurricular activities in smkn 4 weeks can be categorized as "Very good". the answer is categorized as yes as many as 27 questions. The questions categorized as answers are not as many as 13 questions.Key Words: Pancasila Values, Scout Extracurricular